National Readmissions Database characterization of post-cholecystectomy care for inpatients: Readmissions and bile duct repair - Hill, Sarah E.M.; Jensen, Hanna K.; Reif, Rebecca; Karim, Saleema A.; Sexton, Kevin W.; Kalkwarf, Kyle J.; Giorgakis, Emmanouil; Burdine, Lyle (The American journal of surgery, 2021)
•According to the US National Readmissions Database:•Inpatient Laparoscopic Cholecystectomy accounted for 84.5% of cholecystectomy procedures with a 7% readmission rate, 0.0027% had an injury code, 0.46% required biliary to enteric anastomosis or biliary repair, and 2.98% required radiographic intervention (ERCP, PTC, IR Drain).•InpatientOpen Cholecystectomy accounted for 15.5% of all cholecystectomy procedures with a 14% readmission rate, 0.25% had an injury code, 6.27% required biliary to enteric anastomosis or biliary repair, and 5.8% required radiographic intervention (ERCP, PTC, IR Drain).